Perlindungan Hukum terhadap Anak sebagai Pelunasan Utang yang Menjadi Korban Eksploitasi Melalui Perkawinan Paksa - Novenia Cecilia Nadeak; Nayla Hasana (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2025)
Forced marriage of children as debt repayment is an exploitative practice that violates human rights principles and child protection as stipulated in the 1945 Constitution, the Child Protection Law, and the Sexual Violence Criminal Law. This study uses a normative juridical method with a legislative and conceptual approach to examine legal views on the position of children in debt repayment, the relationship between unregistered marriages and forced marriage, and the forms of legal protection that can be provided to victims. The results of the analysis show that children cannot be used as objects of debt repayment because they are not included in the category of property according to the Civil Code, while the practice of unregistered marriage, which is often used as a shortcut, is not recognized by positive law. Forced marriage of children is classified as a form of economic and sexual exploitation that is subject to criminal sanctions. Therefore, it is necessary to limit the grounds for marriage dispensation, prohibit unregistered marriages for minors, and strengthen the implementation of regulations and public awareness campaigns to ensure the protection of children's rights and prevent similar practices in the future.